Ład przestrzenny w gospodarce i współpracy transgranicznej Dolnego Śląska i Saksonii - Adamczuk, Franciszek (Spatial Regularity in Economy and in Trans-Border Cooperation of the Province of Lower Silesia and the Province of Saxony, 2005)
This article concerns problems of the spatial regularity in economy. Two regions have been analysed the Province of Lower Silesia and the Province of Saxony. Most important conditions of creating the "new economic order" in these regions have been introduced, and discussed in the context of present documentation regarding the spatial economy after Poland joined the European Union. Conclusions drawn from the analysis are included in the final part of the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 179-185